1996
DOI: 10.1097/00043426-199611000-00003
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Fibrinolysis After Adding Low Doses of Plasminogen Activators and Plasmin Generation with and without Oxidative Inactivation of Plasmin Inhibitors in Newborns and Adults

Abstract: Our data indicate a more rapid clot lysis at low UK and rt-PA concentrations in newborns despite significantly reduced plasminogen levels. The results of the plasmin generation experiments suggest a diminished effect of plasmin inhibitors towards fetal plasmin, which raises an explanation for the concentration-related differences in the clot lysis assay. The experience with thrombolytic agents in newborns is limited. Most dosage regimens for thrombolytic therapy in children or adults consist of an initial bolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 36 publications
1
14
0
2
Order By: Relevance
“…[28] Reis et al used microtiter clot lysis assay for comparing in vitro fibrinolysis between newborns and adults. [29] Both studies demonstrated a more active fibrinolytic system in the neonates, and their findings are compatible with our current results. Unlike our rapid, feasible technique, those studies employed complicated laboratory tests.…”
Section: Discussionsupporting
confidence: 93%
“…[28] Reis et al used microtiter clot lysis assay for comparing in vitro fibrinolysis between newborns and adults. [29] Both studies demonstrated a more active fibrinolytic system in the neonates, and their findings are compatible with our current results. Unlike our rapid, feasible technique, those studies employed complicated laboratory tests.…”
Section: Discussionsupporting
confidence: 93%
“…One possible reason for the results of the clot lysis experiments is an alteration of the reaction kinetics between fetal plasmin and plasmin inhibitors. Direct comparison of plasmin generation with and without oxidative inactivation of plasmin inhibitors demonstrated a diminished inhibitory effect of plasmin inhibitors toward fetal plasmin, 14 which provides an explanation for the more rapid clot ly sis in newborns at low plasminogen activator concentra tions, where the inhibitors play a more potent role.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 In contrast, fibrin clot lysis was faster and more efficient in new borns compared with adults at low concentrations of rt-PA and urokinase (UK). 14 suits of the clot lysis experiments is the diminished in hibitory effect of plasmin inhibitors toward fetal plasmin. 14 Although there are data on plasma clot lysis in newborns, the potential for dissolution of whole blood clots has not been explored.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The same group of investigators also presented in vitro data indicating a more rapid clot lysis at low urokinase and rt-PA concentrations in newborns despite significantly reduced plasminogen levels. [69] Based on these observations it is un- Table I © Adis International Limited. All rights reserved.…”
Section: Systemic Versus Local and High Dose Versus Low Dose Thrombomentioning
confidence: 99%